The Extent of Imam al-Bukhari’s Influence on the Iraqi School of Hadith and his Influence on it: Analytical and Critical Study - Al-Ziadah, Haifa M.; Al-Azzam, Najah M. (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: To show the extent to which Imam Al-Bukhari influenced and influenced by the Iraqi School of Hadith, by exploring his scientific trips to the main cities and metropolises of Iraq. Another objective is to mention the most prominent Iraqi sheikhs and their impact on shaping Al-Bukhari’s Hadith personality, and to show the most prominent of his students who learned from him in this pioneering school and its impact on the formulation and refinement of their scientific personalities. Methods: It is represented by tracing the threads of the issue in the books that are concerned with mentioning the scientific journeys of scholars in their pursuit for hadith. An analytical and critical approachs are applied by analyzing and criticizing that information to find out the extent of Imam Bukhari’s influence on and being influenced by the Iraqi school. Results: Imam Al-Bukhari seemed independent in his unique critical mentality, as he relied on himself more than on his sheikhs in judging the narrators and their narrations. Conclusions: The study recommends that the scientific and academic circles pay attention to what is related to the Iraqi Hadith School, in terms of identifying it’s approaches, its most prominent scholars, and its influence and impact on other schools.